Parents’ View on Online Education during Covid-19 Pandemic in Nepal: Narrative Analysis - Basnet, Saraswati; Basnet, Hom Bahadur; Bhattarai, Dilip Kumar (Bouddhik Abhiyan (बौद्धिक अभियान), 2022)
Nearly 77 million children, has taken away their classrooms for the past 18 months in the pandemic. School children worldwide have lost 1.8 trillion hours and counting of in-person learning due to COVID-19 lockdowns. At least 1 in 3 school children had no access to remote learning during school closures. Narrative review of Analysis was prepared by using secondary data of the all international and national published journal, report and articles. The narrative review analysis was done only on; a) English language b) involved sample of at least 10 subjects and diverse research design were eligible. Main finding of analysis is to parents as key partners of the efficiency of remote learning during COVID-19. Parent’s participation has played an equalizing role explanatory some of the limitations of remote learning. Difficulties in completing distance learning tasks at home, with major difficulties being children’s lack of learning interests and home environment related limitations. Many parents perceived that the pandemic as an opportunity for family relations, and more research possibilities related to the personal interests of their child as well as focused on the development of their child’s technological skills. Parents found themselves in the place of teachers’ shoes with the arrival of COVID-19 due to shutting down of school. Parents and caregivers face significant gaps in the knowledge and resources needed to help their children with school. They faced challenges of limited access to reliable electricity, affordable internet, and internet-capable devices were major barriers in helping their children continue education remotely.